Anthracycline-induced cardiotoxicity: A multicenter randomised trial comparing two strategies for guiding prevention with enalapril: The International CardioOncology Society-one trial. (May 2018) - Cardinale, Daniela; Ciceri, Fabio; Latini, Roberto; Franzosi, Maria Grazia; Sandri, Maria Teresa; Civelli, Maurizio; Cucchi, GianFranco; Menatti, Elisabetta; Mangiavacchi, Maurizio; Cavina, Raffaele; Barbieri, Enrico; Gori, Stefania; et al.
Abstract: Background: Troponin changes over time have been suggested to allow for an early diagnosis of cardiac injury ensuing cancer chemotherapy; cancer patients with troponin elevation may benefit of therapy with enalapril. It is unknown whether a preventive treatment with enalapril may further increase the benefit. Methods: The International CardioOncology Society-one trial (ICOS-ONE) was a controlled, open-label trial conducted in 21 Italian hospitals. Patients were randomly assigned to two strategies: enalapril in all patients started before chemotherapy (CT; 'prevention' arm), and enalapril started only in patients with an increase in troponin during or after CT ('troponin-triggered' arm). Troponin was assayed locally in 2596 blood samples, before and after each anthracycline-containing CT cycle and at each study visit; electrocardiogram and echocardiogram were done at baseline, and at 1, 3, 6 and 12-month follow-up. Primary outcome was the incidence of troponin elevation above the threshold. Findings: Of the 273 patients, 88% were women, mean age 51 ± 12 years. The majority (76%) had breast cancer, 3% had a history of hypertension and 4% were diabetic. Epirubicin and doxorubicin were most commonly prescribed, with median cumulative doses of 360 [270–360] and 240 [240–240] mg/m 2, respectively. The incidence of troponin elevation was 23% in the prevention and 26% in the troponin-triggered group (p = 0.50). Three patients (1.1%) -two in the prevention, one in the troponin-triggered group-developed cardiotoxicity, defined as 10% point reduction of LV ejection fraction, with values lower than 50%. Interpretation: Low cumulative doses of anthracyclines in adult patients with low cardiovascular risk can raise troponins, without differences between the two strategies of giving enalapril. Considering a benefit of enalapril in the prevention of LV dysfunction, a troponin-triggered strategy may be more convenient. Highlights: No differences were observed between preventiveor troponin-triggered enalapril-based. 1-year incidence of cardiovascular events was very low in patients without heart disease and low doses of anthracyclines. Considering a benefit of enalapril in theprevention of LV dysfunction, a troponin-triggered strategy may be more convenient.